Implementation and Analysis of authentication protocols in the transmission of information by radiofrequency - Callataxi Suárez, Juan David (2021)
In recent years, radio frequency identification (RFID) has become one of the most widely used technologies for the storage and transmission of data in various applications such as inventory control, user access systems, personal information storage, among others. The fundamental purpose of RFID technology is to transmit the identity of an object using radio waves. However, the devices used to send information like radiofrequency readers and RFID tags are vulnerable to various types of attacks. There are a number of measures to safeguard the security of RFID device operations and communications. One of the most important is the authentication protocols. The objective of this project is to evaluate two authentication protocols.% The first one is an RFID flyweight authentication protocol and the second is a lightweight low-cost authentication protocol. through the implementation of algorithms that generate pseudo-random numbers for data transmission, and that comply with the resource restrictions that RFID tags have. These protocols must meet certain standards such as being robust against external threats and light for implementation in passive RFID tags. The first part of the project is the implementation of the protocols in integrated circuits of particular use through the use of VHDL programming language, and ModelSim software for the simulation of the circuits. Both protocols use a pseudorandom number generator algorithm, which provides the information with greater protection to the detection, mainly of the RFID tags. Once the implementation of the protocols has been carried out, in the second part of the project, the data obtained is analyzed mainly data related to the LUT, slices, Flip-flops necessary for the implementation of the protocols and power consumption through the Altera Quartus II and ISE Xilinx Design Suite tool. This allows analyzing and comparing which of the implemented protocols is better adapted to the needs and mainly to the limitation of resources in the RFID tags.